Studia Doctoralia 2020
DOI: 10.47040/sd0000086
|View full text |Cite
|
Sign up to set email alerts
|

The role of personality in the relationship between financial stress and well-being in young people

Abstract: The present study is aimed to study the moderating role of personality in the relationship between financial stress and well-being in young people in Romania. The sample consisted of 168 young people aged between 20 and 35 years old (M = 22.05, AS = 2.72), of which 116 are female (69%) and 52 male (31%). To measure the variables, we used InCharge Financial Distress/Financial Well-Being Scale, The Satisfaction with Life Scale and questionnaires of ten items each (Markers Big Five) that are part of the collectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…With regard to the relation between sport coaches' subjective vitality and motivation for coaching, in line with research guided by SDT that has shown that higher levels of psychological well-being (i.e., subjective vitality or self-esteem) are associated with more self-determined motivation [27,29,30], it was expected that subjective vitality would have been positively related to intrinsic motivation and negatively related to extrinsic motivation.…”
Section: H6mentioning
confidence: 81%
See 2 more Smart Citations
“…With regard to the relation between sport coaches' subjective vitality and motivation for coaching, in line with research guided by SDT that has shown that higher levels of psychological well-being (i.e., subjective vitality or self-esteem) are associated with more self-determined motivation [27,29,30], it was expected that subjective vitality would have been positively related to intrinsic motivation and negatively related to extrinsic motivation.…”
Section: H6mentioning
confidence: 81%
“…In particular, psychological well-being (i.e., in terms of sense of vitality or self-esteem) can be a consequence of intrinsic motivation, but, at the same time, it can promote this type of motivation. For instance, some authors have underlined that increased subjective well-being is associated with intrinsic motivation [27,29,30] and that low levels of psychological well-being are likely to be associated with extrinsic motivation [31].…”
Section: Sport Coaches' Motivation For Coaching and Basic Psychologic...mentioning
confidence: 99%
See 1 more Smart Citation